Bacteriological profile of intra-abdominal infections in a tertiary care hospital - Sukanya Sudhaharan; Padmaja Kanne; Lakshmi Vemu; Padmasri Chavali; Shanker Rao Desmukha; Bheerappa Nagari (Iranian Journal of Microbiology, 2018)
Background and Objectives: Intra-abdominal infections (IAIs) include a wide spectrum of pathological conditions, ranging from uncomplicated appendicitis to fecal peritonitis .The resulting infections should be diagnosed early and treated based on the organism isolated and its susceptibility. In this study the bacteriological profile and antimicrobial resistance pattern of intra-abdominal infections was analyzed. Materials and Methods: A retrospective analysis of samples received from 119 cases of intra-abdominal infections in our Institute from January 2015 to December 2017 was analyzed. Patients with primary peritonitis from cirrhosis or ascites were not included in the study. The specimens were primarily processed, as per standard methods. Identification and antimicrobial susceptibility testing was done by the Vitek-2 system. Anaerobic culture was performed on 5% sheep blood agar plates and incubated in GEN bag anaerobic pouches. Results: In our study perforative peritonitis 43/119 (36.1%) was predominant IAI followed by acute pancreatitis 14/119 (11.7%) and pancreatic necrosis 12/119 (10%). Microbial growth was observed in 66.3% (79/119) of the cases and combined infections were observed in14/119 (11.7%) of the cases. Escherichia coli was the predominant organism isolated in 58/119 (40.8%), out of which 41/58 (70.6%) were ESBL producers and 16 /58 (27.5%) were multi drug resistant isolates. Klebsiella pneumoniae was isolated from 11/119 (9.2%) cases out of which 8/11 (72.7%) were ESBL and 3/11 (27.2%) were multidrug resistant isolates. Post-operative complications was observed in 12/119 (10%) patients with mortality in 15/119 (12.6%) patients. Conclusion: Early diagnosis and appropriate management of the infections will help to prevent the morbidity and mortality associated with these infections.